In vitro regeneration and phytochemical evaluation of pippali (Piper longum) for conservation and therapeutic applications - ARIJITA MOHANTY; JYOTI PRAKASH SAHOO; KAILASH CHANDRA SAMAL (The Indian Journal of Agricultural Sciences)
The present study was carried out during 2021–2022 at College of Agriculture, Odisha University of Agriculture and Technology, Bhubaneswar, Odisha with two varieties of Pippali (Piper longum L.) to establish a standardized protocol for in vitro regeneration, mass multiplication and biochemical characterization in a climber and a local creeper variety. An efficient and reproducible procedure for clonal multiplication via callus regeneration was successfully developed. Murashige and Skoog (MS) medium supplemented with 2 mg/L BAP and 0.5 mg/L K in induced optimal shoot induction, producing 4–5 shoots/1 cm node cutting. Organogenic calli (120 mg/explant) with an 80% induction frequency were obtained from the basal portions of in vitro-grown plantlets on MS medium supplemented with the same concentration of BAP and Kin. The combination of 2 mg/L BAP and 0.5 mg/L IBA yielded the highest number of shoots and promoted spontaneous rooting on the same medium. A high survival rate (95%) was observed following two weeks of hardening. The creeper variety demonstrated steady growth in height, leaf production and fruit yield, while the climber exhibited delayed but robust fruit set. Comparative biochemical profiling showed that the climber variety had higher protein content in both fruit and leaf tissues compared to the creeper, along with significant differences in glycine and phenol levels. High-performance thin-layer chromatography (HPTLC) analysis revealed that the highest piperine content (100, 260.4 AU, 2.62%) was present in the fruit extract of the creeper variety using ethanol, while the lowest piperine content (5,816.4 AU, 0.15%) was detected in the leaf extract of the creeper variety using methanol. Infrared (IR) absorption analysis identified functional groups such as alcohols, amides, alkanes and carboxylic acids. Notable peaks were observed at 3,343.39/cm and 1,253.02/cm in the leaves of the climber variety, and at 3,340/cm and 2,118.46/cm in the leaves of the creeper variety. These findings highlight the potential of pippali as a valuable source of bioactive compounds with significant pharmaceutical applications.